2013
DOI: 10.3390/e15031118
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Large-Scale Quantization in Space Plasmas

Abstract: Abstract:In plasmas, Debye screening structures the possible correlations between particles. We identify a phase space minimum h * in non-equilibrium space plasmas that connects the energy of particles in a Debye sphere to an equivalent wave frequency. In particular, while there is no a priori reason to expect a single value of h * across plasmas, we find a very similar value of h * ≈ (7.5 ± 2.4)×10 −22 J·s using four independent methods:(1) Ulysses solar wind measurements, (2) space plasmas that typically res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 50 publications
(58 reference statements)
3
68
0
Order By: Relevance
“…Then, we show that the standard deviation of the position in the charge distribution of the plasma is given by √ < x 2 > ∼ = λ D , as was arrived at by different means by Livadiotis and McComas (2013a). This result is for 1-D shielding (d = 1), while for any d, the positional variance and standard deviation becomes…”
Section: The Third Interpretation Of the Debye Lengthmentioning
confidence: 50%
See 1 more Smart Citation
“…Then, we show that the standard deviation of the position in the charge distribution of the plasma is given by √ < x 2 > ∼ = λ D , as was arrived at by different means by Livadiotis and McComas (2013a). This result is for 1-D shielding (d = 1), while for any d, the positional variance and standard deviation becomes…”
Section: The Third Interpretation Of the Debye Lengthmentioning
confidence: 50%
“…The physical meaning of the Debye length 343 2001; Saito et al 2000;Leubner 2004;Raadu and Shafiq 2007;Hellberg et al 2009;Livadiotis and McComas 2009, 2010a-c, 2011a, 2011b, 2012, 2013aTribeche et al 2009;Le Roux et al 2010;Eslami et al 2011;Kourakis et al 2012;Yoon 2012;Yoon et al 2012;Bains et al 2013;Saberian and Esfandyari-Kalejahi 2013).…”
Section: And Zelenyi 2000mentioning
confidence: 99%
“…Livadiotis and McComas (2013c) recently began developing this concept for non-equilibrium space plasmas, and showed that a Debye sphere of correlated particles is characterized by a minimum energy exchange and lifetime, leading to a large-scale phase-space quantization, 12 orders of magnitude larger than the Planck constant.…”
Section: Statistical Mechanics and Thermodynamics Of Space Plasmasmentioning
confidence: 99%
“…The 1-particle kappa distribution of energy can be associated with the waiting time distributions of explosive events (Livadiotis and McComas 2013c).…”
Section: Applicationsmentioning
confidence: 99%
“…) Kappa distributions describe numerous space plasma populations. Several examples are the following: (i) the inner heliosphere, including solar wind (e.g., Maksimovic et al, 1997;Pierrard et al, 1999;Mann et al, 2002;Marsch, 2006;Zouganelis, 2008;Štverák et al, 2009;Livadiotis and McComas, 2013a;Yoon, 2014;Pierrard and Pieters, 2015;Pavlos et al, 2016), solar spectra (e.g., Dzifčáková and Dudík, 2013;Dzifčáková, et al, 2015), solar corona (e.g., Owocki and Scudder, 1983;Vocks et al, 2008;Lee et al, 2013;Cranmer, 2014), solar energetic particles (e.g., Xiao et al, 2008;Laming et al, 2013), corotating interaction regions (e.g., Chotoo et al, 2000), and related solar flares (e.g., Mann et al, 2009;Livadiotis and McComas, 2013b;Bian et al, 2014;Jeffrey et al, 2016); (ii) planetary magnetospheres, including magnetosheath (e.g., Formisano et al, 1973;Ogasawara et al, 2013), magnetopause (e.g., Ogasawara et al, 2015), magnetotail (e.g., Grabbe, 2000), ring current (e.g., Pisarenko et al, 2002), plasma sheet (e.g., Christon, 1987;Wang et al, 2003;Kletzing et al, 2003), magnetospheric substorms (e.g., Hapgood et al, 2011), aurora (e.g., Ogasawara et al, 2017), magnetospheres of giant planets, such as Jovian (e.g., Collier and Hamilton, 1995;…”
Section: Introductionmentioning
confidence: 99%